A particular form of Saturn kilometric radiation at the low end of its spectrum - Fischer, G.; Taubenschuss, U.; Pisa, D.; Lamy, L.; Wu, S.; Ye, S.-Y.; Jackman, C. M.; O'Dwyer, E. (My University, 2023)
We studied the spectral morphology of Saturn kilometric radiation (SKR) with the Cassini RPWS (Radio and Plasma Wave Science) instrument and found a particular structure at very low frequencies which we nicknamed "caterpillar" due to its shape and look in dynamic spectra. In this paper we want to present the main physical characteristics of this newly identified form of SKR at the low end of its spectrum. Caterpillars are coarse SKR structures lasting for several hours at frequencies mostly below 40 kHz and with a typical bandwidth of about 10^15 kHz. The latter feature makes them easily distinguishable from Saturn narrowband emissions. Some of the caterpillars are connected to the main SKR emission at higher frequencies and some not. Their polarization is often opposite to that of the main SKR emission, and their total polarization degree is lower. We found almost 600 caterpillar emissions throughout the Cassini mission, and they were preferentially observed from beyond a distance of 10 Saturn radii in the equatorial plane or at lower latitudes. At high time resolution caterpillars show a smooth spectral structure, and only the so-called striations were sometimes found being superimposed.
Planetary, Solar and Heliospheric Radio Emissions IX
PUBLISHED